Prophétismes africains: le Harrisme en Côte-d'Ivoire - Bureau, René (Archives de sciences sociales des religions, 1976)
This paper analyses the contents and meaning of a modem religions movement. The prophet William Harris, a native of Liberia, accomplished his mission in the Ivory Coast in 1915. The Harrist religion developed subsequently and became structured in the 1950s. The appearance of the prophet and his prophetism can be explained on the basis of belief in black and white "witcheraft" : the prophet asumes both and goes further. He thus proposes a new vision of the African world which assimilates the white men's "secrets" and holds ont the hope of attaining their power.